Televisión social en series de ficción y nuevos roles del documentalista audiovisual: el caso de ‘El Ministerio del Tiempo’ - Rodríguez Mateos, David (2015)
New and multiple access devices and distribution channels to audiovisual content has led to the emergence of the phenomenon known as ‘second screen’ and the existence of more proactive and participatory consumption of audiovisual products by consumers. We make a bibliographic review on the concepts of social television and audience, transmedia storytelling and the new roles of audiovisual archivists on the generation of added value on audiovisual products, especially in social audiences deferred in time. To this end we have analized the television serie The Ministry of Time, premiered the public Spanish television  La 1 - TVE. We collected and analyzed more than 30,000 tweets sent with some of the hashtags used by producers and consumers of the television serie. The results show a high dispersion in the number of authors, a concentration of a few authors that send many tweets and a vast majority who just send one or two tweets but represent over 90% of all the tweets sent. We also conducted an analysis of both, hashtags and content analysis of the messages showing some terms and words that show the degree of consumer satisfaction with the serie and the positive sentiment to some of the characters.